PENGARUH STRUKTUR MODAL, MODAL KERJA DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2018 - Nashirudi, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2020)
The rapid economic development in the current era of globalization has an impact on competition in the business world which is getting tighter and tighter. Competition is used as an effort by the company to further improve its performance so that the company's goals can be achieved. To realize these goals, companies must be able to maximize profits from the company. This can be seen from the company's ability to earn profits through the profitability ratio. Profitability is the ability of a company to make maximum use of its resources in generating income that exceeds its expenses. The purpose of this research is to test empirically the effect of capital structure, working capital and company size on profitability in manufacturing companies listed on the Indonesia Stock Exchange. The period of this research is 2016-2018. This type of research is a quantitative study with a research design in the form of a causal associative study. The research population includes all manufacturing companies that have gone public, are listed and active on the Indonesia Stock Exchange during 2016-2018. The sample selection technique used a purposive sampling method and research data were obtained by 15 companies. The data analysis method used is descriptive analysis and multiple linear regression analysis. The results of this study indicate: Debt to Equity Ratio (DER) has a negative and significant effect on Return on Assets (ROA). Working Capital Turnover (WCTO) has a positive and significant effect on Return on Assets (ROA). Firm Size does not affect Return on Assets (ROA). F test results obtained calculated F value of 2.962 with sig. equal to 0.043 which means that the independent variables simultaneously influence and can be used to predict the dependent variable. Adjusted R Square value of 0.118, this means that Return on Assets (ROA) is influenced by Debt-to-Equity Ratio (DER), Working Capital Turnover (WCTO) and Firm Size of 11.8%, while the remaining 80.2% is explained by variables outside the model not examined in this study.